Eriophorum angustifolium and Lolium perenne metabolic adaptations to metals- and metalloids-induced anomalies in the vicinity of a chemical industrial complex - Anjum, Naser A. (2018)
As plants constitute the foundation of the food chain, concerns have been raised about the possibility of toxic concentrations of metals and metalloids being transported from plants to the higher food chain strata. In this perspective, the use of important phytotoxicity endpoints may be of utmost significance in assessing the hazardous nature of metals and metalloids and also in developing ecological soil screening levels. The current study aimed to investigate the role of glutathione (GSH) and its associated enzymes in the metabolic adaptation of two grass species namely Eriophorum angustifolium Honck. and Lolium perenne L. to metals and metalloids stress in the vicinity of a chemical industrial complex (Estarreja, Portugal). Soil and plant samples were collected from contaminated (C) and non-contaminated (reference, R) sites, respectively, near and away from the Estarreja Chemical Complex, Portugal. Soils (from 0 to 10 and 10 to 20 cm depths) were analyzed for pH, organic carbon, and metals and metalloids concentrations. Plant samples were processed fresh for physiological and biochemical estimations, while oven-dried plant samples were used for metals and metalloids determinations following standard methodologies. Both soils and plants from the industrial area exhibited differential concentrations of major metals and metalloids including As, Cu, Hg, Pb, and Zn. In particular, L. perenne shoot displayed significantly higher and lower concentrations of Pb and As, respectively at contaminated site (vs. E. angustifolium). Irrespective of sites, L. perenne shoot exhibited significantly higher total GSH pool, oxidized glutathione (GSSG) and oxidized protein (vs. E. angustifolium). Additionally, severe damages to photosynthetic pigments, proteins, cellular membrane integrity (in terms of electrolyte leakage), and lipid peroxidation were also perceptible in L. perenne shoot. Contrarily, irrespective of the sites, activities of catalase and GSH-regenerating enzyme, GSH reductase, and GSH-metabolizing enzymes such as GSH peroxidase and GSH sulfotransferase were significantly higher in shoot of E. angustifolium. Despite the higher total GSH content, L. perenne is vulnerable to multi-metals-induced stress in comparison to E. angustifolium as depicted by increased GSH- and protein oxidation, low reactive oxygen radical-processing potential (exhibited in terms of low catalase activity) and poor GSH pool utilization efficiency (in terms of lower GSH-associated enzymes activities). The outcome of the present study may be significant for understanding vital GSH-mediated metals and metalloids tolerance mechanisms in plants as well as their unsuitability for animal consumption due to higher metals and metalloids burdens.